2006
DOI: 10.1002/rcm.2667
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fluorotelomer alcohols by liquid chromatography/tandem mass spectrometry in water

Abstract: Fluorotelomer alcohols (FTOHs) are important polyfluorinated raw materials that belong to the general category of perfluoroalkyl substances (PFAS). PFAS, including perfluoroalkyl carboxylates (PFCAs) and perfluoroalkyl sulfonates, have recently attracted considerable attention because they are persistent and found globally in the environment. FTOHs are precursors that may degrade in the environment to PFCAs. The development of analytical methods for determination FTOHs in environmental samples is necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
2
21
2
1
Order By: Relevance
“…The 8:2 and 10:2 FTUCAs (concentrations up to 15.1 ng/L) were observed in samples collected from four lakes in the Canadian Arctic [166]. In addition, a method for the extraction and analysis of FTOHs in water has also been developed by Szostek, Prickett and Buck [184], but it has yet to be applied to real-life samples.…”
Section: Surface Watersmentioning
confidence: 99%
“…The 8:2 and 10:2 FTUCAs (concentrations up to 15.1 ng/L) were observed in samples collected from four lakes in the Canadian Arctic [166]. In addition, a method for the extraction and analysis of FTOHs in water has also been developed by Szostek, Prickett and Buck [184], but it has yet to be applied to real-life samples.…”
Section: Surface Watersmentioning
confidence: 99%
“…However, accurate mass fragment and neutral loss analysis conclusively provided the formula C 12 is was submitted as the lead candidate with high con dence (Score= 0.90) along with two equally consistent but less common alkyl isomers (assigned lower scores).…”
Section: Resultsmentioning
confidence: 99%
“…A reference negative ion electrospray CID tandem mass spectrum for 8-2 uorotelomer alcohol was found that matched the provided data very well. 12) A er a SciFinder search of the formula to investigate potential isomers, 8-2 uorotelomer alcohol was Fig. 4.…”
Section: )mentioning
confidence: 99%
“…Therefore, it is recommended to avoid headspace in sampling bottles [51], and kept samples at low temperature after collection [44,45,52]. Szostek et al studied the stability of PFTOHs in water under different storage conditions [53]. In this work it was concluded that aqueous samples can safely be stored in the freezer using glass vials and sealed with a septum lined with alumina foil.…”
Section: Sampling Process and Preservationmentioning
confidence: 93%
“…In this work it was concluded that aqueous samples can safely be stored in the freezer using glass vials and sealed with a septum lined with alumina foil. In addition, no biodegradation or biotransformation was observed under these conditions [53]. On the other hand, also it was studied the possible benefices associated with the use of biological inhibitors (such as formalin) to preserve the samples, but it was found that some suppress the MS responses during the analysis [54], and therefore should be avoided.…”
Section: Sampling Process and Preservationmentioning
confidence: 99%